Noriega Varela and the Portuguese Language from his Correspondence with Teixeira de Pascoaes - Freixeiro Mato, Xosé Ramón (Madrygal. Revista de Estudios Gallegos, 2018)
This work begins with the functional distribution of Galician and Spanish uses in the work by Noriega Varela, dealing firstly with his literary language and secondly with the language of his correspondence. Its next section approaches the relation of the Galician poet with Portuguese writers, especially with Teixeira de Pascoaes. Finally, the use of Castilian in letters to him will be analysed taking into account his proficient knowledge of Portuguese, finally concluding that such use obeys to ideological reasons.
Keywords: Noriega Varela; Teixeira de Pascoaes; Portuguese; Galician; Spanish; Correspondence.